A Room-Temperature Stable Y(II) Aryloxide: Using Steric Saturation to Kinetically Stabilize Y(II) Complexes - Moehring, Samuel A.; Miehlich, Matthias; Hörger, Christopher; Meyer, Karsten; Ziller, Joseph W.; Evans, William J. (Inorganic Chemistry, 2020)
The utility of the bulky aryloxide ligands 2,6-Ad2-4-Me-C6H2O- (Ad,Ad,MeArO-) and 2,6-Ad2-4-t-Bu-C6H2O- (Ad,Ad,t-BuArO- Ad = 1-adamantyl) for stabilizing the Y(II) ion is reported and compared with the results with 2,6-t-Bu2-4-Me-C6H2O- (Ar′O-). In contrast to the reduction product obtained from reducing Y(OAr′)3 with potassium graphite, which is only stable in solution for 60 s at room temperature, KC8 reduction of Y(OArAd,Ad,t-Bu)3 in THF in the presence of 2.2.2-cryptand (crypt) produces the room-temperature stable, crystallographically characterizable Y(II) aryloxide [K(crypt)][Y(OArAd,Ad,t-Bu)3]. The X-band EPR spectrum at 77 K shows an axial pattern with resonances centered at g= 1.97 and g= 2.00 and hyperfine coupling constants of A = 156.5 G and A= 147.8 G and at room temperature shows an isotropic pattern with giso = 1.98 and Aiso = 153.3 G, which is consistent with an S = 1/2 spin system with nuclear spin I = 1/2 for the 89Y isotope (100% natural abundance).
CRIS-Team Scopus Importer:2020-03-06